What Is Effective Aid? How Would Donors Allocate It? - Kenny, Charles (2012)
There are significant weaknesses in some of the traditional justifications for assuming that aid will foster development. This paper looks at what the cross-national aid effectiveness literature suggests about effective aid, first in terms of promoting income growth and then for promoting other goals. This review forms the basis for a discussion of recommendations to improve aid effectiveness and a discussion of effective aid allocation. Given the multiple potential objectives for aid, there is no one right answer. However, it appears that there are a number of reforms to aid practices and distribution that might help to deliver a more significant return to aid resources.